2019
DOI: 10.1155/2019/1489751
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy in Noncommunicating Rudimentary Horn of Unicornuate Uterus: A Case Report and Review of the Literature

Abstract: Pregnancy implanted in the rudimentary horn of unicornuate uterus is very rare with an incidence of 1 in 75,000 to 1 in 150,000 pregnancies. Both prerupture and postrupture diagnosis of ectopic pregnancy in the rudimentary horn of a unicornuate uterus is difficult. Here is a case of a 21-year-old gravida 5 para 3 abortion 1 mother presented with abdominal pain of 2 days duration following a falling accident. The patient was severely anemic and was in hypovolemic shock at the time of presentation. She had diffu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 9 publications
0
14
0
5
Order By: Relevance
“…Emergency open surgery with multiple blood transfusions is the only option. 14,15 But with advent of better diagnostics, and more women being diagnosed in first trimester scans, medical line of management with surgical removal being done on a later date has become possible. 5 There are no fixed guidelines to manage such ectopics, but like management of other ectopic pregnancy, in early hemodynamically stable pregnancy, intrauterine or intramuscular methotrexate, or intrauterine KCL can be injected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emergency open surgery with multiple blood transfusions is the only option. 14,15 But with advent of better diagnostics, and more women being diagnosed in first trimester scans, medical line of management with surgical removal being done on a later date has become possible. 5 There are no fixed guidelines to manage such ectopics, but like management of other ectopic pregnancy, in early hemodynamically stable pregnancy, intrauterine or intramuscular methotrexate, or intrauterine KCL can be injected.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier days, or in places where access to health care is difficult, when diagnosis is a problem, women often come with rupture of rudimentary horn with unstable hemodynamic condition. Emergency open surgery with multiple blood transfusions is the only option 14,15 . But with advent of better diagnostics, and more women being diagnosed in first trimester scans, medical line of management with surgical removal being done on a later date has become possible 5 .…”
Section: Discussionmentioning
confidence: 99%
“…However, as mentioned previously, the term cornual pregnancy has been used in clinical practice to describe pregnancies in various locations, both normally sited and ectopics, and we decided to abandon this term as suggested by Baltarowich (2017) . Rudimentary horn pregnancy is rare, with a reported incidence of 1 in 75 000–150 000 pregnancies ( Tesemma, 2019 ). If not diagnosed in early pregnancy, they can advance well into the second trimester, when they often present with severe pain and rupture ( Jayasinghe et al , 2005 ; Li et al , 2019 ).…”
Section: Recommendationsmentioning
confidence: 99%
“…[ 5 10 ] To treat these cases, emergency laparotomy is performed. Apart from detecting hypovolemic shock,[ 11 12 13 14 15 16 17 ] patients frequently have abdominal pain,[ 7 11 13 14 15 16 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 ] but some reports have indicated that only 8% of rudimentary horn pregnancies (RHPs) are diagnosed before the symptoms appear. [ 44 ] Sufficient knowledge seems necessary to detect NCRHP during early obstetric screening.…”
Section: Introductionmentioning
confidence: 99%